Penilaian Kualiti Perkhidmatan Pusat Kesihatan Masyarakat (PUSKESMAS) Di Wilayah Sumatera Utara, Indonesia - Santosa, Heru (2010)
Public Health Center (PUSKESMAS) is a leading health service facility in the development of community health in Indonesia and plays a vital role to realize the vision of Healthy Indonesia 2010. This research was conducted in the North Sumatera region with the objectives to evaluate the health service quality of PUSKESMAS; to identify the effect of input, process and environmental factors on PUSKESMAS health service quality; to assess the difference in health service quality between urban and rural PUSKESMAS; to investigate the demand and need of the community; and to design an instrument for evaluating the health service quality of PUSKESMAS.